Convenience Effects of Mobile Payment Systems in Retail Stores: Evidence from a Region in Zhejiang Province - Shanshan, Wang; Ricafort, Reagan (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examines the impact of mobile payment systems on the operational performance of small retail stores, with a focus on convenience and business outcomes. Grounded in the Technology Acceptance Model and SERVQUAL Model, the research explores how perceived usefulness, ease of use, and service quality influence merchant experiences and performance. A mixed-methods design was employed, consisting of a quantitative survey and qualitative interviews based on five service dimensions—tangibility, reliability, responsiveness, assurance, and empathy. The study involved 317 retail store respondents, and statistical analyses, including Pearson correlation and regression, were used to assess relationships among variables. The findings reveal that all dimensions of mobile payment convenience—transaction operations, business management, and customer service—are positively and significantly correlated with performance indicators such as cost changes, profitability, and crisis management capability. However, the effects are not uniform and vary according to the store’s years of operation, indicating that adoption outcomes depend on the firm’s developmental stage. The study also identifies that mobile payment systems reshape rather than reduce cost structures and that perceived convenience is closely linked to practical operational improvements, including reduced friction and enhanced customer interactions. The study concludes that mobile payment systems function as integrated operational tools that enhance efficiency and resilience but require usability optimization and effective business integration. These findings align with Sustainable Development Goal 8 (Decent Work and Economic Growth) by supporting improved business efficiency and productivity, and SDG 9 (Industry, Innovation, and Infrastructure) through the adoption of digital financial technologies. The sustainability impact lies in promoting operational efficiency, reducing transaction friction, and supporting the long-term resilience and competitiveness of small retail enterprises through digital transformation.
Keywords: Business performance; Convenience; Crisis management capability; Mobile payment systems; Profitability; Retail stores; SERVQUAL model; Technology Acceptance Model